PENGARUH EXPERIENTIAL MARKETING DAN CUSTOMER RELATIONSHIP MANAGEMENT TERHADAP LOYALITAS KONSUMEN DALAM MELAKUKAN PEMBELIAN KEMBALI SEPEDA MOTOR HONDA PADA PT CAPELLA DINAMIK NUSANTARA TEMBESI BATAM - Jurnal Akuntansi Barelang (LPPM Universitas Putera Batam, 2017)
Research purpose was to understand the effect of experiental marketing and customer relationship management strategy to customer loyalty in the repurchasing the Honda motorcycles at PT Capella Dinamik Nusantara Tembesi Batam. Questionaire was used as main data collection instrument. Total respondent are 109 and the sampling method was purposive. The result was tested with product moment for validity test and cronbach alpha was used to test the reliability. Data was analysed using path analysis. Result indicated that experiental marketing signifficantly affected customer loyalty (β=0,219). Customer relationship management significantly affected customer loyalty (β=0,318). Experiental marketing signifficantly affected repurchase both directly (β=0,208) and indirectly (β= 0,287). Customer relationship management significantly affected repurchase both directly (β=0,211) and indirectly (β=0,326). Customer loyalty signifficantly affected repurchase (β=0,362).